Factors influencing reoperation following breast‐conserving surgery. Issue 9 (15th May 2018) - Philpott, Andrew; Wong, Joshua; Elder, Kenneth; Gorelik, Alexandra; Mann, G. Bruce; Skandarajah, Anita
Abstract : Background: Reoperation rates after breast‐conserving surgery are highly variable and the best techniques for optimizing margin clearance are being evaluated. The aim was to identify the reoperation rate at our centre and identify influential factors, including a change in guidelines on margin recommendations and the introduction of in‐theatre specimen X‐ray. Methods: A retrospective review of medical records was undertaken to identify 562 patients who underwent breast conservation at The Royal Melbourne Hospital and Royal Women's Hospital between 2013 and 2015. All cases that underwent subsequent re‐excision or total mastectomy were captured and factors influencing margin excision recorded. Results: Reoperation was undertaken in 19.5% of patients (110; 86 re‐excisions and 24 total mastectomies). There was a reduction in reoperation rate from 25% to 17% ( P = 0.01) with adoption of the margin guidelines in 2014, but no significant reduction with the introduction of in‐theatre specimen X‐ray in 2015 (21% versus 16%, P = 0.14). On multivariate analysis, factors that significantly influenced reoperation rates were the presence of multifocality on mammogram (odds ratio (OR): 5.3, 95% confidence interval (CI): 1.6–16.7, P < 0.01); lesion size on mammogram (OR: 2.2 per 10 mm, 95% CI: 1.4–3.6, P < 0.01); smaller excision specimen weight (OR: 0.5 per 25 g of resection, 95% CI: 0.3–0.8, P < 0.01); and pure ductal carcinoma in situ on final pathology (OR: 5.9, 95% CI: 1.9–16.7, P < 0.01). Conclusion: Optimizing reoperation rates following breast‐conserving surgery remains a surgical challenge, particularly in patients with in situ or multifocal disease. Adoption of international margin guidelines reduced reoperation rates at our centre; however, introduction of intraoperative specimen X‐ray had no influence.